Entropic Entanglement: Information Prison Break - Alexander Y. Yosifov; Lachezar G. Filipov (Advances in High Energy Physics)
We argue that certain nonviolent local quantum field theory (LQFT) modification considered at the global horizon (r=2M) of a static spherically symmetric black hole can lead to adiabatic leakage of quantum information in the form of Hawking particles. The source of the modification is (i) smooth at r=2M and (ii) rapidly vanishing at r≫2M. Furthermore, we restore the unitary evolution by introducing extra quanta which departs slightly from the generic Hawking emission without changing the experience of an infalling observer (no drama). Also, we suggest that a possible interpretation of the Bekenstein-Hawking bound as entanglement entropy may yield a nonsingular dynamical horizon behavior described by black hole thermodynamics. Hence, by treating gravity as a field theory and considering its coupling to the matter fields in the Minkowski vacuum, we derive the conjectured fluctuations of the background geometry of a black hole.